2008
DOI: 10.1074/jbc.m801716200
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Induces Autophagy of Human Myeloid Leukemia Cells

Abstract: Vitamin D3 causes potent suppression of various cancer cells; however, significant supraphysiological concentrations of this compound are required for antineoplastic effects. Current combinatorial therapies with vitamin D3 are restricted to differentiation effects. It remains uncertain if autophagy is involved in vitamin D3 inhibition on leukemia cells. Here we show that besides triggering differentiation and inhibiting apoptosis, which was previously known, vitamin D3 triggers autophagic death in human myeloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 50 publications
6
98
0
Order By: Relevance
“…Thus, Beclin 1 is a crucial regulator of autophagy and apoptosis in infected cells, because of its role as a member of the Beclin 1/Vps34 complex and its participation in the antiapoptotic complex Beclin 1-Bcl-2, competing with Bad for the binding to Bcl-2. 44 To summarize, the data presented here show that Cb infection is favored by overexpressed Beclin 1 and that depletion of this protein, as well as of the overexpressed Bcl-2, alters the normal development of CRVs. Furthermore, our results suggest the existence of a functional interaction between the autophagic and apoptotic pathways in infected cells, to avoid apoptosis induction and to trigger the autophagy pathway, allowing the survival and development of Cb.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, Beclin 1 is a crucial regulator of autophagy and apoptosis in infected cells, because of its role as a member of the Beclin 1/Vps34 complex and its participation in the antiapoptotic complex Beclin 1-Bcl-2, competing with Bad for the binding to Bcl-2. 44 To summarize, the data presented here show that Cb infection is favored by overexpressed Beclin 1 and that depletion of this protein, as well as of the overexpressed Bcl-2, alters the normal development of CRVs. Furthermore, our results suggest the existence of a functional interaction between the autophagic and apoptotic pathways in infected cells, to avoid apoptosis induction and to trigger the autophagy pathway, allowing the survival and development of Cb.…”
Section: Discussionmentioning
confidence: 96%
“…This notion is supported by results obtained in myeloid leukemia cells, in which the knockdown of Beclin 1 activates apoptosis. 44 These researchers have shown that Beclin 1 acts as a negative regulator of apoptosis because it competes with the pro-apoptotic protein Bad, for binding to the anti-apoptotic protein Bcl-X L , implying that the complex Beclin 1-Bcl-X L has indeed an anti-apoptotic role. 44 In addition, it has recently been reported that dexamethasone induces autophagy in murine T-cell lymphoma line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in HBV (hepatitis B virus)-infected hepatocytes, the HBV x protein increases autophagy by up-regulating the expression of Beclin 1 [160]. In human monocytes and human myeloid leukemia cells, vitamin D3 has been shown to induce autophagy by up-regulating both Beclin 1 and Atg5 [161,162]. The transcription factor implicated has not been identified, but it has been shown that in human monocytes the effect of Vitamin D3 is mediated via cathelicidin.…”
Section: Nf-κbmentioning
confidence: 99%
“…Novel anti-cancer therapeutic compounds activating the autophagic pathway are not limited to the species previously stated. In addition to these, (96,97) some derivatives of naphthalimide were found to be potent inhibitors of lymphoid leukemia in murine models [82] while vitamins D3 and K2 were shown to inhibit human myeloid leukemias [83,84]. Glucocorticoids such as dexamethasone also contributed to autophagic death in leukemia of lymphoid origin [85,86].…”
Section: Contribution Of Autophagy To Cell Deathmentioning
confidence: 99%